Case Studies on Food and Agribusiness Closed Membership Cooperatives - Boland, Michael; Katz, Jeff; Barton, David (My University, 1999)
This publication uses case studies to explain vertical coordination and other food and agribusiness closed membership cooperatives.
MF2448_1999_12
Keywords: MF2448; Economics; MF